THE CONTRIBUTIONS OF IMÉM ABU BAKR AHMAD IBN ALI IBN AL-RAZI AL-JAÎÉÎ IN FIQH: AN ANALYTICAL STUDY WITHIN THE CONTEXT OF HANAFÊ JURISPRUDENCE - Zeeshan Ali; Abid Saeed; Kashif Mehmood Qureshi (Journal of Religion and Society, 2025)
ImÉm Abu Bakar al-JaÎÉÎ is famous jurist of HanafÊ school of thought. He wrote a great interpretation of QurÉn named AhkÉm al QurÉn. He has written more than fifteen books and more than eight book related to HanafÊ school of thought. In his interpretation of Quran, he doesn’t interpret all Qur’anic verses, as is done by other commentators. This article provides a comprehensive research analysis of the juristic contributions of Abu Bakr Ahmad ibn Ali al-Razi al- JaÎÉÎ within the context of Hanafi jurisprudence. Al- JaÎÉÎ, a prominent Islamic scholar of the 10th century, significantly advanced the development and proliferation of Hanafi fiqh. The research examines his technique, his works, and the influence of his legal interpretations on later Hanafi thought. The study conducts a thorough analysis of his principal treatises, particularly his work on HanafÊ school of thought to explore the conceptual framework that influenced his legal reasoning. It underscores how his jurisprudential perspectives aided in addressing intricate matters in Islamic law, reconciling classic HanafÊ doctrine with contemporary legal procedures. The paper highlights the enduring impact of al- JaÎÉÎ on the HanafÊ School and Islamic law through an examination of his scholarly methodology. This research aims to deepen knowledge of the historical and intellectual legacy of al- JaÎÉÎ in the broader framework of Islamic legal thought. Keywords: Contributions of ImÉm JaÎÉÎ, HanafÊ, Jurisprudence